Positive electrode for energy storage devices and energy storage devices

JP2026170682APending Publication Date: 2026-10-22UNIV OKAYAMA +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025064378
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-04-09
Publication Date
2026-10-22

AI Technical Summary

Benefits of technology

【0009】 本開示によれば、高容量と優れた電気特性とを両立する蓄電デバイス用正極及び蓄電デバイスを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026170682000001_ABST
    Figure 2026170682000001_ABST
Patent Text Reader

Abstract

This invention provides a positive electrode for energy storage devices and an energy storage device that achieve both high capacity and excellent electrical characteristics by using aluminum as the negative electrode. [Solution] The energy storage device (capacitor 1) comprises a positive electrode 12 having a positive electrode active material layer 16 containing porous carbon with a pore size of 2 nm to 4 nm and a positive electrode current collector 15 made of tungsten, a negative electrode 13 containing aluminum, and a separator 14 holding an electrolyte consisting of an ionic liquid containing a Lewis acid containing aluminum atoms and a Lewis base. The specific surface area of ​​the porous carbon is 1000 m². 2 / g~4000m 2 The concentration is / g, and the electrolyte is 1-ethyl-3-methylimidazolium tetrachloroaluminate.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a positive electrode for an energy storage device and an energy storage device. [Background technology]

[0002] Capacitors and secondary batteries are used as energy sources for electronic devices and electric vehicles. In recent years, research and development of aluminum batteries using aluminum as the negative electrode has been progressing (see, for example, Patent Document 1). [Prior art documents] [Patent Documents]

[0003] [Patent Document 1] Japanese Patent Publication No. 2018-041670 [Overview of the Initiative] [Problems that the invention aims to solve]

[0004] As the applications of energy storage devices expand, there is a growing demand for even higher capacities. Furthermore, good charging characteristics are also required.

[0005] The purpose of this disclosure is to provide a positive electrode for an energy storage device and an energy storage device that achieve both high capacity and excellent electrical characteristics. [Means for solving the problem]

[0006] The aspects of this disclosure that solve the above problems are as follows:

[0007] (1) A positive electrode for an energy storage device comprising a positive electrode active material layer containing porous carbon with a pore size of 2 nm to 4 nm.

[0008] (2) In the positive electrode for the energy storage device described in (1) above, the specific surface area of ​​the porous carbon is 1000 m 2 / g~4000m 2 / g is also acceptable. (3) An energy storage device comprising a positive electrode having a positive electrode active material layer containing porous carbon with a pore size of 2 nm to 4 nm, a negative electrode containing aluminum, and an electrolyte. (4) In the energy storage device described in (3) above, the electrolyte may be an ionic liquid containing a Lewis acid containing aluminum atoms and a Lewis base. (5) In the energy storage device described in (4) above, the electrolyte may be 1-ethyl-3-methylimidazolium tetrachloroaluminate. (6) The energy storage device described in any one of (3) to (5) above has a capacity of 80 mAh / g or more per unit mass of the positive electrode active material layer, and the impedance measured using the AC impedance method may be 12 Ω or less. [Effects of the Invention]

[0009] According to this disclosure, it is possible to provide a positive electrode for an energy storage device and an energy storage device that achieve both high capacity and excellent electrical characteristics. [Brief explanation of the drawing]

[0010] [Figure 1] This is an exploded perspective view showing an example of a capacitor. [Figure 2] This graph shows the charge and discharge characteristics of the capacitor in Example 1 for each current density value. [Figure 3] This graph shows the charge and discharge characteristics of the capacitor in Example 2 for each current density value. [Figure 4] This graph shows the charge and discharge characteristics of the capacitor in Comparative Example 1 for each current density value. [Figure 5] This graph shows the charge and discharge characteristics of the capacitor in Comparative Example 2 for each current density value. [Figure 6] This graph shows the charge and discharge characteristics of the capacitor in Comparative Example 3 for each current density value. [Figure 7] This graph shows the charge and discharge characteristics of the capacitor in Comparative Example 4 for each current density value. [Figure 8]This is a graph showing the charge-discharge characteristics of the capacitor of Comparative Example 5 for each current density value. [Figure 9] This is a graph showing the results of cyclic voltammetry measurement. [Figure 10] This is a graph showing a Nyquist diagram illustrating the results of AC impedance measurement. [Modes for Carrying Out the Invention]

[0011] Hereinafter, preferred embodiments of the present disclosure will be described in detail. However, the present disclosure is not limited to the following embodiments. The elements listed below can be arbitrarily combined, and the scope of the present invention is intended to include all modifications within the scope of the claims and the scope equivalent to the claims. The upper limit values and lower limit values in each numerical range of the embodiments of the present disclosure can be arbitrarily combined to constitute any numerical range.

[0012] [Positive Electrode for Electricity Storage Device] The positive electrode for an electricity storage device according to the present embodiment includes a positive electrode active material layer containing porous carbon with a pore size of 2 nm to 4 nm as a positive electrode active material. The pore size of the porous carbon in the present embodiment means the average value of the pore sizes of the pores in the porous carbon (that is, the average pore size). The pore size of the porous carbon in the present embodiment can be calculated from the pore size distribution obtained by analyzing a nitrogen adsorption isotherm by the LDFT method (Non-Local Density Functional Theory).

[0013] The porous carbon as the positive electrode active material has a relatively large surface area, and is capable of adsorbing and desorbing electrolyte ions contained in the electricity storage device on the surfaces of the pores. Capacitance is exhibited by the adsorption and desorption of electrolyte ions.

[0014] Although the details of why the positive electrode for the energy storage device disclosed herein and the energy storage device using it exhibit superior capacity and electrical characteristics are unclear, it is presumed to be due to the following mechanism. By setting the pore diameter of the porous carbon used in the positive electrode to the range of 2 nm to 4 nm, the surface area of ​​the porous carbon can be increased, thereby increasing capacity. Furthermore, by setting the pore diameter of the porous carbon to the range of 2 nm to 4 nm, an appropriate number of electrolyte ions can move smoothly through each pore formed in the carbon material, reducing diffusion resistance and enabling rapid adsorption and desorption. Therefore, it is presumed that electrical characteristics such as high output can be improved. In addition, by setting the pore diameter of the porous carbon to the range of 2 nm to 4 nm, reactions due to the insertion and desorption of electrolyte ions can be suppressed, thereby improving electrical characteristics such as high output. If the pore diameter is smaller than 2 nm, electrolyte ions cannot enter the pores, making adsorption and desorption to the pores difficult. When the pore diameter exceeds 4 nm, excess electrolyte ions enter the pores, resulting in the presence of electrolyte ions within the pores that do not contribute to the formation of the electrical double layer. This hinders the movement of electrolyte ions within the pores, increasing the diffusion resistance.

[0015] Activated carbon is preferred as the porous carbon used in the positive electrode active material layer. While there are no particular limitations on the raw materials for the porous carbon, examples include wood, sawdust, coconut shells, polyacrylonitrile-based materials, cellulose-based materials, phenolic resin-based materials, petroleum-based pitch, and coal-based pitch. The shape of the porous carbon is not particularly limited, and examples include powder, granular, and fibrous forms. Porous carbon may be used alone or in combination of two or more types. Porous carbon may also contain additives such as nitrogen and silicon.

[0016] The pore size of the porous carbon is preferably 2 nm to 3 nm, more preferably 2.3 nm to 2.8 nm.

[0017] The specific surface area of ​​porous carbon is preferably 1000 m² from the viewpoint of increasing capacity and improving electrical properties. 2 / g~4000m 2 / g, more comfortably 2000m 2 / g~3800m 2 / g, more preferably 2400m 2 / g~3500m 2 / g. The specific surface area of the porous carbon in the present embodiment can be calculated by performing analysis by the BET method from a nitrogen adsorption isotherm.

[0018] The total pore volume of the porous carbon is preferably 0.5cm, from the viewpoints of higher capacity and improved electrical characteristics 3 / g~3.0cm 3 / g, more preferably 1.3cm 3 / g~1.8cm 3 / g. The total pore volume of the porous carbon in the present embodiment can be calculated from the pore distribution obtained by performing analysis by the LDFT method (non-local density functional theory) from a nitrogen adsorption isotherm.

[0019] The porous carbon can be obtained by a known production method. Examples of the production method for the porous carbon include a pyrolysis method, an activation method, a coating method, a vapor deposition method and the like, and the activation method is preferred. As the porous carbon, a commercially available product can also be used. Examples of the commercially available porous carbon include Maxsorb (registered trademark) MSA-20, MSC-30 (all manufactured by MC Evo Tech Co., Ltd.) and the like.

[0020] The positive electrode active material layer in the positive electrode for electricity storage devices of the present embodiment preferably further contains a conductive aid, a binder, and a solvent.

[0021] Examples of the conductive aid used in the positive electrode active material layer include carbon blacks such as acetylene black (AB) and Ketjen black, carbon fibers such as carbon nanotubes (CNT) and carbon nanofibers, graphite and the like, carbon black is preferred, and acetylene black (AB) is more preferred. The conductive aids may be used singly or in combination of two or more.

[0022] Examples of binders used in the positive electrode active material layer include polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), polytetrafluoroethylene (PTFE), and styrene-butadiene rubber (SBR), with polyvinylidene fluoride (PVDF) being preferred. The binder may be used alone or in combination of two or more types.

[0023] Examples of solvents used in the positive electrode active material layer include non-aqueous solvents such as N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide, methanol, ethanol, and acetone, with NMP being preferred. The solvent may be used alone or in combination of two or more.

[0024] The content of porous carbon in the entire positive electrode active material layer is preferably 55% to 90% by mass, more preferably 65% ​​to 85% by mass, and even more preferably 75% to 85% by mass, from the viewpoint of increasing capacity and improving electrical properties. When two or more types are used in combination, the content refers to the total amount.

[0025] The content of the conductive additive relative to the entire positive electrode active material layer is preferably 3% to 20% by mass, more preferably 5% to 15% by mass. When two or more types are used in combination, the content refers to the total amount.

[0026] The binder content relative to the entire positive electrode active material layer is preferably 3% to 20% by mass, more preferably 5% to 15% by mass. When two or more binders are used in combination, the content refers to the total amount.

[0027] The solvent content relative to the entire positive electrode active material layer is preferably 0.1% to 5% by mass, more preferably 0.5% to 3% by mass. When two or more solvents are used in combination, the content refers to the total amount.

[0028] In the positive electrode active material layer, the mass ratio of porous carbon, conductive additive, and binder (porous carbon:conductive additive:binder) is preferably 70-90:5-15:5-15, and more preferably 80:10:10. Within the above range, the ratio of each component in the positive electrode active material layer can be further increased in capacity and improved in electrical properties.

[0029] A positive electrode for an energy storage device can be manufactured by applying a slurry containing porous carbon, a conductive additive, a binder, and a solvent onto a thin plate-shaped positive electrode current collector, and then drying the solvent in the applied slurry.

[0030] The material of the positive electrode current collector used in the positive electrode of an energy storage device is not particularly limited as long as it is a conductive material that can withstand a predetermined voltage applied to the energy storage device. Examples include molybdenum, tungsten, glassy carbon, chromium nitride, and titanium nitride, with tungsten and titanium nitride being preferred.

[0031] The thickness of the positive electrode active material layer formed on the positive electrode current collector is not particularly limited, but is preferably 1 nm to 100 nm, more preferably 10 nm to 50 nm. The thickness of the positive electrode current collector is not particularly limited, but is preferably 5 μm to 100 μm, more preferably 10 μm to 50 μm.

[0032] The positive electrode for energy storage devices of this embodiment can be suitably used as the positive electrode for energy storage devices. Examples of energy storage devices include secondary batteries such as aluminum-ion secondary batteries and capacitors such as aluminum-ion capacitors. In particular, it is suitable as a positive electrode for capacitors because it has excellent electrical characteristics such as high capacity and high output.

[0033] [Energy storage devices (capacitors)] The energy storage device of this embodiment, which uses the positive electrode for the energy storage device described above, will now be explained. Figure 1 is an exploded perspective view showing an example of a capacitor 1. The capacitor 1 shown in Figure 1 as an example of an energy storage device has a coin shape.

[0034] Capacitor 1 comprises a case 11, a positive electrode 12 housed in the case 11, a negative electrode 13, a separator 14, and an electrolyte (not shown). The positive electrode 12 and the negative electrode 13 are stacked via a separator impregnated with the electrolyte.

[0035] [case] The case 11 used in the capacitor of this embodiment houses and seals the positive electrode 12, negative electrode 13, separator 14, and electrolyte. Examples of materials for the case 11 include polytetrafluoroethylene (PTFE) and polyethylene terephthalate (PET), with polytetrafluoroethylene (PTFE) being preferred.

[0036] [Positive electrode] The positive electrode 12 used in the capacitor 1 of this embodiment is the positive electrode for the energy storage device described above. The positive electrode 12 comprises a positive electrode current collector 15 made of tungsten and a positive electrode active material layer 16 formed on the positive electrode current collector 15, which contains porous carbon, a conductive additive, a binder, and a solvent. Leads (not shown) are electrically connected to any point on the positive electrode current collector 15.

[0037] [Negative electrode] The negative electrode 13 used in the capacitor of this embodiment comprises aluminum foil or aluminum alloy foil. The metal used for the aluminum alloy is preferably one or more selected from, for example, calcium, strontium, barium, and radium. The negative electrode 13 is preferably aluminum foil, and more preferably high-purity aluminum foil (for example, 99.9% by mass or higher purity). The aluminum foil or aluminum alloy foil functions as the negative electrode active material layer and the negative electrode current collector. Leads (not shown) are electrically connected to any point on the aluminum foil or aluminum alloy foil.

[0038] [Electrolyte] The electrolyte used in the capacitor of this embodiment is a non-aqueous electrolyte. An ionic liquid is preferred as the electrolyte, and an ionic liquid containing a Lewis acid containing aluminum atoms and a Lewis base is more preferred. In this specification, "Lewis acid" means a substance that accepts electron pairs, and "Lewis base" means a substance that donates electron pairs.

[0039] Examples of Lewis acidic aluminum compounds contained in ionic liquids include aluminum chloride, aluminum fluoride, aluminum bromide, and aluminum trifluoromethanesulfonate, with aluminum chloride being preferred.

[0040] Examples of Lewis bases contained in ionic liquids include urea compounds, ammonium compounds, pyridine compounds, and imidazolium compounds, with imidazolium compounds being preferred.

[0041] Examples of imidazolium compounds include 1-ethyl-3-methylimidazolium chloride (EMIm-Cl), 1-ethyl-3-methylimidazolium bromide (EMIm-Br), 1-butyl-3-methylimidazolium trifluoromethanesulfonate (BMIm-TfO), and 1-ethyl-3-methylimidazolium trifluoromethanesulfonate (EMIm-TfO), with 1-ethyl-3-methylimidazolium chloride (EMIm-Cl) being preferred.

[0042] Specific examples of ionic liquids include, for example, 1-ethyl-3-methylimidazolium chloride-aluminum chloride (EMImCl-AlCl3), 1-butyl-3-methylimidazolium trifluoromethanesulfonate-aluminum chloride (BMImTfO-Al(TfO)3), triethylammonium chloride-aluminum chloride, tetramethylammonium chloride-aluminum chloride, and pyridine chloride-aluminum chloride. Ionic liquids may be used alone or in combination of two or more types.

[0043] Among the ionic liquids, 1-ethyl-3-methylimidazolium chloride-aluminum chloride (1-ethyl-3-methylimidazolium tetrachloroaluminate) is particularly preferred. The mole fraction of AlCl3 to EMImCl in 1-ethyl-3-methylimidazolium chloride-aluminum chloride (AlCl3:EMImCl) is preferably 1.5:1. In the above ratio, 1-ethyl-3-methylimidazolium chloride-aluminum chloride is an acidic bath, and AlCl7 is an anion that constitutes the ionic liquid. - And, AlCl4 - The numbers of and are equal. 1-ethyl-3-methylimidazolium chloride-aluminum chloride is composed of AlCl4 - Because its three-dimensional structure is well-suited to the 2nm to 4nm pore size of the porous carbon in the positive electrode, it is smoothly adsorbed and desorbed, thus further improving its electrical properties.

[0044] [Separator] The separator 14 used in the capacitor of this embodiment is placed between the positive electrode and the negative electrode. The separator 14 holds the electrolyte mentioned above. As the separator 14, porous resin films such as polyethylene and polypropylene, nonwoven fabrics, and glass fibers are preferably used.

[0045] The thickness of the separator 14 is preferably 1 μm to 50 μm, more preferably 10 μm to 30 μm, from the viewpoint of preventing short circuits between the positive and negative electrodes, electrolyte retention, and energy density.

[0046] In this embodiment, the capacitor preferably has a capacitance per unit mass of the positive electrode active material layer of 80 mAh / g or more, more preferably 90 mAh / g or more, and even more preferably 100 mAh / g or more.

[0047] The capacitor of this embodiment preferably has an impedance of 12Ω or less, more preferably 11Ω or less, and even more preferably 10Ω or less, measured using the AC impedance method at a temperature of 25°C and a frequency of 0.1Hz.

[0048] The capacitor 1 of this embodiment can be manufactured by inserting the positive electrode 12's positive electrode active material layer 16 and the negative electrode 13's negative electrode active material layer into a case 11 with a separator 14 interposed between them, sealing a portion of the case 11, filling it with an electrolyte, and then sealing the case 11.

[0049] The energy storage device of this embodiment is not limited to a capacitor, but may also be a secondary battery. The energy storage device of this embodiment achieves both high capacity and excellent electrical characteristics by using porous carbon with a specific pore size as the positive electrode active material. The energy storage device of this embodiment can be used for various applications, such as industrial, mobile, and backup power supplies. [Examples]

[0050] The present invention will be described in more detail below based on examples and comparative examples, but the present invention is not intended to be limited to those examples.

[0051] [Example 1] (Fabrication of positive electrode for capacitor) 600 mg of activated carbon PC1 (Maxsorb MSA-20, manufactured by MC Evatec Co., Ltd.) and 75 mg of acetylene black (AB) were weighed out as porous carbon, and 2-5 mL of N-methyl-2-pyrrolidone (NMP) was added. The mixture was then stirred and mixed for 30 minutes using an ultrasonic homogenizer. Next, 75 mg of polyvinylidene fluoride (PVDF) was weighed out, 3 mL of NMP was added, and the mixture was stirred and mixed for 30 minutes using an ultrasonic homogenizer to dissolve the PVDF. Then, the PVDF solution was poured into the PC / AB mixture and stirred and mixed using a magnetic stirrer at 25°C for 12 hours to obtain the slurry of Example 1. The mixing ratio (mass ratio) of each component constituting the positive electrode active material layer was porous carbon:AB:PVDF = 80:10:10.

[0052] The obtained slurry was applied to a tungsten substrate (16 mm in diameter, 100 μm thick, disc-shaped) to be used as a positive electrode current collector. After drying at 25°C for 12 hours, it was vacuum-dried at 25°C for 12 hours, and then vacuum-dried again at 120°C for 12 hours to produce the positive electrode of Example 1.

[0053] (Capacitor fabrication) A glass fiber filter paper separator (GF / D, manufactured by Cytiva) was used to laminate the positive electrode of Example 1 with a 99+% purity aluminum foil (16 mm in diameter, 25 μm thick, disc-shaped) as the negative electrode. The laminated components were then placed in a coin-shaped case made of polytetrafluoroethylene. Finally, ionic liquid 1-ethyl-3-methylimidazolium chloride-aluminum chloride (EMIm-Cl / AlCl3) (manufactured by Sigma-Aldrich) was added as the electrolyte to fabricate the coin-shaped capacitor cell of Example 1. The capacitor was fabricated inside a glove box.

[0054] [Example 2, Comparative Examples 1-5] The cathodes and capacitors using them for Example 2 and Comparative Examples 1-5 were fabricated in the same manner as in Example 1, except that the porous carbon materials were designated as PC2-7. Details of PC2-7 are as follows. PC2: Activated carbon, Maxsorb MSC-30, manufactured by MC Evatec Co., Ltd. PC3: Activated carbon, YP-50F, manufactured by Kuraray Co., Ltd. PC4: Activated carbon, Maxsorb MSP-20, manufactured by MC Evatec Co., Ltd. PC5: Knobel MJ(4)030-00, manufactured by Toyo Tanso Co., Ltd. PC6: Knobel MJ(4)010-00, manufactured by Toyo Tanso Co., Ltd. PC7: Knobel MH-00, manufactured by Toyo Tanso Co., Ltd.

[0055] <Evaluation of porous carbon and capacitors> [Measurement of the specific surface area of ​​porous carbon] For the porous carbons of Examples 1 and 2 and Comparative Examples 1 to 5, an automatic specific surface area / pore distribution analyzer (BELSORP-mini, manufactured by Microtrac-Bel Co., Ltd.) was used to dry the carbonaceous material under vacuum conditions at 200°C for 24 hours, and then measure the nitrogen adsorption isotherm under conditions of 77K using liquid nitrogen. The nitrogen adsorption isotherm was analyzed using the BET method with analysis software (BELMaster) to calculate the BET specific surface area of ​​the porous carbon. The results are shown in Table 1.

[0056] [Method for measuring the average pore size of porous carbon] For the porous carbon samples of Examples 1 and 2 and Comparative Examples 1 to 5, the nitrogen adsorption isotherms obtained by the method described above were analyzed using the NLDFT method with analysis software (BELMaster) to determine the pore size distribution and calculate the average pore size. The results are shown in Table 1.

[0057] [Method for measuring the total pore volume of porous carbon] For the porous carbon samples of Examples 1 and 2 and Comparative Examples 1 to 5, the nitrogen adsorption isotherms obtained by the method described above were analyzed using the NLDFT method with analysis software (BELMaster) to determine the pore size distribution and calculate the total pore volume. The results are shown in Table 1.

[0058] [Method for measuring volume] The charge-discharge characteristics of the capacitors in Examples 1 and 2 and Comparative Examples 1 to 5 were measured at a temperature of 25°C using a potentiometer galvanostat (SP-150 and VSP-300, manufactured by Biologic). Specifically, as an aging treatment, constant current charging was performed up to 2.2V at a current density of 0.05A / g, followed by constant current discharging down to 0.01V at a current density of 0.05A / g for 50 cycles. After the aging treatment, a charge-discharge test was performed by constant current charging up to 2.2V at a current density of 0.1A / g, followed by constant current discharging down to 0.01V at a current density of 0.1A / g. The discharge capacity was measured from the discharge curve obtained from the charge-discharge test. Similarly, constant current charge-discharge tests were performed at current densities of 0.2A / g, 0.5A / g, and 1.0A / g. Table 1 shows the measured discharge capacity per unit mass of the positive electrode active material layer at a current density of 0.1 A / g. Furthermore, the charge-discharge characteristics of each capacitor from Examples 1 and 2 and Comparative Examples 1 to 5 are shown in graphs in Figures 2 to 8 for each current density value. In Figures 2 to 8, the horizontal axis of the graphs represents the capacity per unit mass of the positive electrode active material layer (mAh / g), and the vertical axis represents the cell voltage (V).

[0059] [Method for measuring cyclic voltammetry (CV)] Cyclic voltammetry was measured for the capacitors of Examples 1 and 2 and Comparative Examples 1 to 5 at a temperature of 25°C using a potentiogalvanostat (SP-150 and VSP-300, manufactured by Biologic). The results of the cyclic voltammetry measurements are shown in the graph in Figure 9.

[0060] [Method for measuring AC impedance] For the capacitors of Examples 1 and 2 and Comparative Examples 1 to 5, AC impedance measurements were performed at a temperature of 25°C using a potentiometer galvanostat (SP-150 and VSP-300, manufactured by Biologic), and the cell resistance was measured. The AC impedance test conditions were a frequency band of 0.1 Hz to 1 MHz and an amplitude of 10 mV. The Nyquist plot showing the results of the AC impedance measurement is shown in the graph of Figure 10. The figure shown below Figure 10 is an enlarged view of the divided region indicated by the rectangular frame in the graph. The impedance measurement results at 0.1 Hz are shown in Table 1.

[0061] [Table 1]

[0062] As is clear from Table 1 and Figures 2-8, the capacitors of Examples 1 and 2, which use porous carbon with pore diameters in the range of 2 nm to 4 nm, exhibit high capacitance and low impedance, resulting in excellent electrical characteristics. The capacitors of Examples 1 and 2 also have large specific surface areas. On the other hand, the capacitors of Comparative Examples 1 and 2, which use porous carbon with pore diameters of less than 2 nm, have a relatively large specific surface area, but low capacitance and high impedance, resulting in poor electrical characteristics. The capacitor of Comparative Example 3 has a small specific surface area and low capacitance. The capacitors of Comparative Examples 4 and 5 have a relatively high capacitance, but high impedance, resulting in poor electrical characteristics.

[0063] As is clear from Figures 2-8, the capacitors of Examples 1 and 2 have linear discharge curves, indicating that capacitance is generated by ion adsorption and desorption over most voltage ranges. Furthermore, Figure 9 shows that the capacitance value of the capacitors of Examples 1 and 2 remains constant over most voltage ranges. Therefore, high capacitance, high output, and high cycle characteristics can be achieved. On the other hand, the capacitors of Comparative Examples 1-5 show a curved discharge curve around 1.5V, suggesting that an oxidation-reduction reaction is occurring. [Explanation of Symbols]

[0064] 1. Capacitor (energy storage device) 11 cases 12 Positive electrode 13 Negative electrode 14 Separator

Claims

1. The positive electrode active material layer contains porous carbon with a pore size of 2 nm to 4 nm. Positive electrode for energy storage devices.

2. The specific surface area of ​​the porous carbon is 1000 m². 2 / g to 4000m 2 / g A positive electrode for an energy storage device according to claim 1.

3. A positive electrode comprising a positive electrode active material layer containing porous carbon with a pore size of 2 nm to 4 nm, A negative electrode containing aluminum, Equipped with electrolytes Energy storage device.

4. The electrolyte is an ionic liquid containing a Lewis acid containing aluminum atoms and a Lewis base. The energy storage device according to claim 3.

5. The electrolyte is 1-ethyl-3-methylimidazolium tetrachloroaluminate. The energy storage device according to claim 4.

6. The capacity per unit mass of the positive electrode active material layer is 80 mAh / g or more. The impedance measured using the AC impedance method is 12 ohms or less. The energy storage device according to claim 3 or claim 4.

Citation Information

Patent Citations

  • Aluminum battery

    JP2018041670A